Nitrate supplementation attenuates As(V) toxicity in Solanum lycopersicum L. cv Pusa Rohini Insights into As(V) sub-cellular distribution, photosynthesis, nitrogen assimilation, and DNA damage - Gupta, Praveen (Plant physiology and biochemistry : PPB, 2019)
Copyright © 2019 Elsevier Masson SAS. All rights reserved.